2002
DOI: 10.1038/sj.bjc.6600353
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein B gene variations enhance susceptibility to squamous cell carcinoma of the lung in German patients

Abstract: Genetic factors are thought to influence the risk for lung cancer. Since pulmonary surfactant mediates the response to inhaled carcinogenic substances, candidate genes may be among those coding for pulmonary surfactant proteins. In the present matched case -control study a polymorphism within intron 4 of the gene coding for surfactant specific protein B was analysed in 357 individuals. They were divided into 117 patients with lung cancer (40 patients with small cell lung cancer, 77 patients with non small cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…These results support that of Seifart et al [2002b] who studied the polymorphism of the SP-B intron-4 in German patients with lung cancer and concluded that the SP-B variants may enhance susceptibility to developing squamous cell carcinoma of the lung [Seifart et al, 2002b]. However, the SP-B variants appear to strongly, enhance the susceptibility to the development of SCC in workers who are exposed to chromate-related processes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results support that of Seifart et al [2002b] who studied the polymorphism of the SP-B intron-4 in German patients with lung cancer and concluded that the SP-B variants may enhance susceptibility to developing squamous cell carcinoma of the lung [Seifart et al, 2002b]. However, the SP-B variants appear to strongly, enhance the susceptibility to the development of SCC in workers who are exposed to chromate-related processes.…”
Section: Discussionsupporting
confidence: 82%
“…Different polymorphisms within the SP-B gene have been described Lin et al, 1999]. Seifart et al [2002b] studied a polymorphism of the SP-B intron-4 and concluded that the Sp-B intron-4 variants may enhance susceptibility to squamous cell carcinoma (SCC) of the lung in German patients.…”
Section: Introductionmentioning
confidence: 99%
“…As variations in SP-B have been associated with respiratory diseases other than COPD [9,10,25], we also tested for association between the three polymorphisms and risk of common pulmonary diseases, such as asthma, pneumonia and lung cancer. We found no consistent association between SP-B genotypes and any of the lung diseases we examined, except for asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the level of methylation, for two out of 11 CpGs studied, appeared, in normal lung tissue, to correlate with SP-A1 and SP-D gene expression. The present data together with the genetic association of surfactant protein genes with lung cancer (24,31,32) indicate that surfactant proteins may contribute to lung cancer genetically and epigenetically.…”
Section: Discussionmentioning
confidence: 93%
“…SP-B and SP-C play a key role in the surface tension lowering activity of surfactant, and SP-A and SP-D are important for the host defense function of the lung. Genetic variants of these genes have been associated with inflammatory lung diseases, such as respiratory distress syndrome (RDS), acute RDS (ARDS), chronic obstructive pulmonary disease (COPD), and lung cancer (19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%